Brain Mapping in Neurosurgery - Guive Sharifi; Abdolkarim Rahmanian; Ghahreman Bemana; Navid Kalani; Ali Kazeminezhad (Iranian Journal of Neurosurgery, 2022)
Background and Aim: Brain mapping is the study of the anatomy and function of the Central Nervous System (CNS). Brain mapping has many techniques and these techniques are permanently changing and updating. From the beginning, brain mapping was invasive and for brain mapping, electrical stimulation of the exposed brain was needed. However, nowadays brain mapping does not require electrical stimulation and often does not require any complex involvement of patients. To perform brain mapping, functional and structural neuroimaging has an essential role. The techniques for brain mapping include noninvasive techniques (structural and functional magnetic resonance imaging [fMRI], diffusion MRI [dMRI], magnetoencephalography [MEG], electroencephalography [EEG], positron emission tomography [PET], near-infrared spectroscopy [NIRS] and other non-invasive scanning techniques) and invasive techniques (direct cortical stimulation [DCS] and intracarotid amytal test [IAT] or wada test). Methods and Materials/Patients: This is a narrative study on brain mapping in neurosurgery. To provide up-to-date information on brain mapping in neurosurgery, we precisely reviewed brain mapping and neurosurgery articles. Using the keywords “brain mapping”, “neurosurgery”, “brain mapping techniques”, and “benefits of brain mapping”, all of the related articles were obtained from Google Scholar, PubMed, and Medline and were precisely studied. Results: To perform an effective and safe neurosurgical intervention, precise information about the structural and functional anatomy of the brain is obligatory. Based on the information on brain mapping, the selection of suitable patients for the operation, the plan of appropriate operative approach, and good surgical results can be acquired. To provide this information, we can use brain mapping techniques that were formerly applied in neuroscientific brain mapping efforts with noninvasive techniques, such as fMRI, MEG, dMRI, PET, etc and invasive techniques, such as DCS, IAT, etc. Conclusion: Functional brain mapping is a constantly evolving fact in neurosurgery. All stages in obtaining a functional image are complex and need knowledge of the basic physiologic and imaging features.